2011
DOI: 10.1038/nn.2859
|View full text |Cite
|
Sign up to set email alerts
|

Neurod6 expression defines new retinal amacrine cell subtypes and regulates their fate

Abstract: Most regions of the central nervous system contain numerous subtypes of inhibitory interneurons that play specialized roles in circuit function. In mammalian retina, the ~30 subtypes of inhibitory interneurons called amacrine cells (ACs) are generally divided into two groups: wide/medium-field GABAergic and narrow-field glycinergic, which mediate lateral and vertical interactions, respectively, within the inner plexiform layer. We used expression profiling and mouse transgenic lines to identify and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 49 publications
12
148
2
Order By: Relevance
“…For example, recent studies have shown that amacrine subtypes arise at distinct times, as predicted by the competence model (38,43), and that further distinctions among them may result from postmitotic fate choices (44). Similarly, analysis of clones containing late-born retinal cell types (rods, amacrines, bipolars, and Müller glia) indicates that stochastic mechanisms acting on a homogeneous population of progenitors can account for the much of the diversity observed (1,45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown that amacrine subtypes arise at distinct times, as predicted by the competence model (38,43), and that further distinctions among them may result from postmitotic fate choices (44). Similarly, analysis of clones containing late-born retinal cell types (rods, amacrines, bipolars, and Müller glia) indicates that stochastic mechanisms acting on a homogeneous population of progenitors can account for the much of the diversity observed (1,45).…”
Section: Discussionmentioning
confidence: 99%
“…RGC and amacrine subtype fate choices, including laminar-targeting decisions, are correlated with and likely specified by birthdate (Cherry et al 2009, De la Huerta et al 2012, Osterhout et al 2014, Voinescu et al 2009). A few transcription factors controlling laminar choice have been identified, but none of these alter IPL stratification without changing other aspects of cell fate, such as neurotransmitter type (Cherry et al 2011, Kay et al 2011. Because choice of presynaptic partner is such a crucial determinant of neuronal function, it is not surprising that mechanisms for specifying it are hardwired as part of a neuron's fate decision.…”
Section: Dendrite Targeting Is Determined Geneticallymentioning
confidence: 99%
“…This pruning falls into the genetically determined category, as manipulation of afferent activity does not alter it (Devaud et al 2003, Lin et al 2000. Neural activity can affect some aspects of RGC dendrite refinement (Bodnarenko et al 1995, Okawa et al 2014, Tian & Copenhagen 2003, but for the most part, IPL sublaminar targeting is not altered by manipulating neural activity (Kerschensteiner et al 2009; for a review, see Kay & Sanes 2013). Therefore, to understand dendrite targeting in these and other cell types throughout the brain, we need to understand genetically determined mechanisms linking cell fate and arbor morphology.…”
Section: Dendrite Targeting Is Determined Geneticallymentioning
confidence: 99%
“…The current model is that the homeodomain TFs PAX6 and SIX3 combined with the bHLH TFs MATH3 and NEUROD together specify a pan-AC identity, with PAX6 and SIX3 conveying positional identity in the INL (13). Other TFs are required for the specification and differentiation of amacrine subtypes, including ISLET1 (ISL1; cholinergic ACs) (4), NR4A2 (GABAergic ACs) (14), EBF family members (glycinergic ACs) (15), NEUROD6 (glycinergic ACs and non-GABAergic nonglycinergic ACs) (16), and BHLHB5 (GABAergic, glycinergic, dopaminergic, and cholinergic ACs) (5,17).…”
Section: Significancementioning
confidence: 99%
“…We considered the possibility that this expanded population of PRKCA + ACs in the Prdm8 EGFP/EGFP retina might express another neurotransmitter marker instead of GAD65: either CHAT, which also labeled more ACs in the Prdm8 mutant (Fig. 6D), or GLYT1, because glycinergic and GABAergic ACs normally account for 85% of the AC population in mature retina (16) (Fig. S6 E-F″).…”
Section: Prdm8 Is Required For the Development Of Amacrine Subtype Idmentioning
confidence: 99%